ULTRASONOGRAPHIC CHARACTERISTICS AND COMPARING WITH FINE-NEEDLE ASPIRATION CYTOLOGY RESULTS OF SUBACUTE GRANULOMATOUS (DE QUERVAIN'S) THYROIDITIS CASES - Nguyễn , Thị Thu Hằng; Lại, Thu Hương; Lê, Văn Khảng (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Purpose: To describe the ultrasound imaging characteristics of subacute thyroiditis and compare them to fine needle aspiration thyroid cytology results.Materials and methods: A retrospective and prospective cross-sectional descriptive study on patients diagnosed with subacute thyroiditis, who underwent ultrasound, and had fine–needle aspiration results at the Radiology Center, Bach Mai Hospital from January 2020 to April 2023.Results: The study was conducted on 65 patients with fine needle aspiration results as subacute thyroiditis, 90.8% female, and 63.1% in middle age (40 to 60 years old). Clinical symptoms including neck pain, low-grade fever, and increased metabolism were observed in 63.1% of cases. 67.7% of cases had heterogeneous hypoechoic lesions, with illdefined margins. In 45 cases Doppler color ultrasound was performed, 44 cases (66.2%) hypovascularity, and only 1 case (1.5%) hypervascularity. 35.4% of cases had hypoechoic thyroid nodules, of which 10.8% were classified as TIRADS 4 and 24.6% were classified as TIRADS 5.Conclusion: Subacute thyroiditis can present as hypoechoic nodules, which can easily be confused with malignancies, challenging in differential diagnosis. Fine-needle aspiration thyroid cytology is an essential procedure in atypical cases. Clinical coordination with imaging and cytology will help achieve an accurate diagnosis.